Analisis Pengaruh Alokasi Dana Desa (Add) Program Pembangunan Desa Terhadap Kesejahteran Masyarakat Desa Di Desa Lakatuli Kecamatan Mataru, Kabupaten Alor - Dina Maniyeni (Peneliti.net, 2023)
Welfare is a condition in which a person or community is in a safe, prosperous, secure state, safe from all kinds of disturbances, problems or difficulties and so on and in this study the aim is to determine the effect of village fund allocation and village development programs on the welfare of village communities, this type of research is quantitative research with data collection techniques namely observation, interviews, and documentation studies. This study used population primary data and the sample was the people of Lakatuli Village, Mataru District, Alor Regency, totaling 73 people. The statistical method used in this study is multiple linear regression. The results of this study indicate that: Partially the village fund allocation variable has a significant value of 0.00 Partially the village development program variable has a significant value of 0.002 where this value is smaller than the alpha value of 0.05 so the results of this study accept H2 which states that the village development program partially has a positive effect on the welfare of village communities in Lakatuli Village, Mataru District, Alor Regency. Simultaneously the variable allocation of village funds and village development programs on the welfare of village communities has a significant value of 0.00 where this value is smaller than the alpha value, namely H3 which states that the variable allocation of village funds and village development programs on the welfare of village communities simultaneously has a positive effect on the welfare of the village community in Lakatuli Village, Mataru District, Alor Regency.